2008
DOI: 10.1186/1471-213x-8-98
|View full text |Cite
|
Sign up to set email alerts
|

Fgfr1 signalling in the development of a sexually selected trait in vertebrates, the sword of swordtail fish

Abstract: Background: One of Darwin's chosen examples for his idea of sexual selection through female choice was the "sword", a colourful extension of the caudal fin of male swordtails of the genus Xiphophorus. Platyfish, also members of the genus Xiphophorus, are thought to have arisen from within the swordtails, but have secondarily lost the ability to develop a sword. The sustained increase of testosterone during sexual maturation initiates sword development in male swordtails. Addition of testosterone also induces s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 74 publications
2
43
0
4
Order By: Relevance
“…; Iovine ; Offen et al . ), so changes to a single gene involved in fin development can potentially influence all fins. Consistent with this idea, our QTL mapping revealed that some QTL were shared among median fins, although we cannot exclude the possibility that multiple linked genes, instead of a single gene, caused the overlap of QTL.…”
Section: Discussionmentioning
confidence: 99%
“…; Iovine ; Offen et al . ), so changes to a single gene involved in fin development can potentially influence all fins. Consistent with this idea, our QTL mapping revealed that some QTL were shared among median fins, although we cannot exclude the possibility that multiple linked genes, instead of a single gene, caused the overlap of QTL.…”
Section: Discussionmentioning
confidence: 99%
“…Gonopodium development is activated by elevated levels of testosterone in poeciliid fish [8], [12], [13], [61] and we show that elevated levels of testosterone induce further developed gonopodia. Several molecular studies support this view: (1) expression of genes involved in fin ray growth, such as msxC , fgfr1 and shh , is induced by testosterone [9], [19], [20]. It has been suggested that androgen signaling acts upstream of a signaling cascade that results in the activation of downstream effectors, such as Fgf-signaling and msxC , to shape the gonopodium [9], [20], (2) androgen receptors ( ars ) are expressed in the developing gonopodium (this study and [19]) and (3) inhibition of androgen signaling down-regulates gene expression and perturbs gonopodium growth [19].…”
Section: Discussionmentioning
confidence: 95%
“…shh and its receptor ptc1 are expressed during gonopodium development of G. affinis and inhibition of shh signaling also blocks gonopodium development [19]. Moreover, fgfr1 and msxC are up-regulated in growing gonopodial rays and are thought to promote gonopodium outgrowth [9], [20]. Experiments by Pickford and Atz (1957) suggest a putative role of thyroid signaling.…”
Section: Introductionmentioning
confidence: 99%
“…In at least some of these species, small vestigial "swordlets" can be restored by exposure to abnormally high levels of testosterone (Gordon et al 1943). In X. maculatus, a swordless species, a single mutation is sufficient to form a similar (although not identical) fin extension, presumably by enhancing cell response to endogenous testosterone (Offen et al 2008). These observations suggest that the pathway responsible for sword development has decayed only partially following the loss of the sword and can be brought back by changes in a relatively small number of genes.…”
Section: Discussionmentioning
confidence: 98%